2016
DOI: 10.1287/msom.2016.0586
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking, Multiarmed Bandits, and the Italian Judiciary

Abstract: We model how a judge schedules cases as a multi-armed bandit problem. The model indicates that a first-in-first-out (FIFO) scheduling policy is optimal when the case completion hazard rate function is monotonic. But there are two ways to implement FIFO in this context: at the hearing level or at the case level. Our model indicates that the former policy, prioritizing the oldest hearing, is optimal when the case completion hazard rate function decreases, and the latter policy, prioritizing the oldest case, is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Projection bias provides a complementary explanation that people overestimate how much they will work. Regarding my results on multi-tasking, Coviello, Ichino, and Persico (2015) and Bray et al (2016) find empirical evidence that it decreases productivity. Coviello, Ichino, and Persico (2014) show that workers may engage knowingly in intrinsically inefficient multi-tasking due to lobbying by co-workers and superiors.…”
Section: Introductionmentioning
confidence: 73%
“…Projection bias provides a complementary explanation that people overestimate how much they will work. Regarding my results on multi-tasking, Coviello, Ichino, and Persico (2015) and Bray et al (2016) find empirical evidence that it decreases productivity. Coviello, Ichino, and Persico (2014) show that workers may engage knowingly in intrinsically inefficient multi-tasking due to lobbying by co-workers and superiors.…”
Section: Introductionmentioning
confidence: 73%
“…In previous work (Coviello et al 2014(Coviello et al , 2015Bray et al 2016) we have shown that judicial workflow management practices, and in particular multitasking, can have a significant impact on judicial productivity. This line of work is distinct from the present paper because workflow management refers to the efficient (or not) scheduling of individual hearings of different cases, whereas the present paper looks at the probability of closing a case in a given hearing, that is, conditional on how the workflow has been managed.…”
Section: Related Literaturementioning
confidence: 95%
“…Cases A and B are adjudicated in their first hearing with probabilities p 1,A , p 1,B > 0, else a second hearing is necessary. In previous work (Coviello et al 2014(Coviello et al , 2015Bray et al 2016) we have shown that it is more efficient to wait until case A is adjudicated before starting on case B. This is workflow management.…”
Section: Related Literaturementioning
confidence: 99%
“…The evidence that does exist provides some indication of what works -successful reforms include training judges on better case flow management in Pakistan (Chemin 2009b); adopting first-in-first-out procedures in Italy (Bray et al 2016); placing time limits on decisions in Senegal (Kondylis and Stein 2018); establishing specialized courts and simplifying procedures in Brazil (Lichand and Soares 2014); providing better information to litigants in Mexico (Sadka, Seira and Woodruff 2018); or implementing a bundle of reforms, including court-appointed mediation, limits on trial duration and adjournments, required affidavit furnishment, and mobile justice in India (Chemin 2009a).…”
Section: Literaturementioning
confidence: 99%